QUALITY OF CHIPS PRODUCED FOR ENERGY PURPOSES IN SOUTHWESTERN PARANÁ - Gomes Caminha, Victor Aurélio; Brun, Eleandro José; Konig Brun, Flávia Gizele; França, Ramiro Faria; da Silva, Valéria Mariano; Braga, Vitória Sena (Floresta, 2024)
Quality of wood chips produced for energy purposes in the southeast region of Paraná. To characterize and monitor the moisture content of the energy biomass used by a food industry in southwestern Paraná-Brazil, the materials of five different providers were analyzed, four were from Eucalyptus spp. and one from Pinus sp. The chips were characterized according to the moisture content on a wet basis, apparent density, calorific value and immediate chemical analysis was performed. With the collected data, calibration curves were generated to adjust the moisture content measurement equipment, MUG M75, used by the company. The calibration of the M75 was made based on the linear regression model, and all chips presented an adequate calibration curve with a coefficient of determination (R²) above 0.9. The chips had a moisture content of 35 to 45% in the humid base. The highest value of apparent density was 207.67 kg.m³. The superior calorific value was statistically equal for all materials, with an average of 4,384.4 kcal/kg. Regarding the immediate chemical analysis, volatiles were between 80 and 84%, for fixed carbon the highest value obtained was 19.16%. The studied chips had low ash contents, with a general average of 0.59%. All calibration curves showed high accuracy (> 90%), showing that the method used can replace oven drying after the recipe is calibrated for suppliers.